HUBUNGAN ANTARA ASUPAN CAIRAN HARIAN DAN MINUMAN ISOTONIK DENGAN TINGKAT HIDRASI ATLET NON-ELITE UKM SEPAK BOLA DI UNIVERSITAS NEGERI SURABAYA - Noor, Rossi Alysia; Pratama, Satwika Arya; Dini, Cleonara Yanuar; Bahar, Asrul (Jurnal Gizi dan Pangan Soedirman, 2024)
The purpose of this study was to describe the amount of daily fluid intake, isotonic drinks, hydration, physical activity, and to determine the relationship between fluid intake with isotonic drinks on the hydration level of non-elite athletes. This study applied cross-sectional design with total sampling method on 25 non-elite football athletes. The instruments used was SQFFQ Beverages for daily fluid intake and isotonic drinks, IPAQ shortform for physical activity levels, and Urine Specific Gravity (USG) for hydration levels. The results of this study found that the average fluid intake of athletes was less (3468.81±1330.34 ml), less isotonic drink intake (548±243.82 ml), hydration level is minimal dehydration (1018.20±7.05 g/dl), and high physical activity level (3009.52±1275.86 MET-minutes/week). Daily fluid intake and hydration levels had a significant relationship (r=0.657, p=0.000), and the relationship between isotonic drinks and hydration level its also significant (r=0.561, p=0.004). The amount of daily fluid intake and isotonic drinks had a significant relationship with athletes' hydration levels.